1994
DOI: 10.1111/j.1365-2265.1994.tb03784.x
|View full text |Cite
|
Sign up to set email alerts
|

A hormonal and radiological evaluation of adrenal gland in patients with acute or chronic pulmonary tuberculosis

Abstract: Adrenal enlargement demonstrated by computerized tomography is common in patients with acute pulmonary tuberculosis, but our findings show that cortisol reserve is normal, in contrast to previous suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
1
28
1
1
Order By: Relevance
“…We did not find adrenocortical insufficiency in these patients, in contrast to previous suggestions [5]. Post et al also reported intact adrenal reserve in active pulmonary tuberculosis [9].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We did not find adrenocortical insufficiency in these patients, in contrast to previous suggestions [5]. Post et al also reported intact adrenal reserve in active pulmonary tuberculosis [9].…”
Section: Discussioncontrasting
confidence: 56%
“…We have recently demonstrated that the adrenal glands are enlarged and cortisol reserve is normal in patients with acute pulmonary tuberculosis [5]. We think that adrenal enlargement during acute pulmonary tuberculosis is due to a stressful condition caused by acute tuberculosis.…”
Section: Tuberculosismentioning
confidence: 99%
“…Since the increment of cortisol was found to be inversely correlated with basal serum cortisol levels, the increment of cortisol was assumed to be inappropriate for the prediction of adrenal sufficiency [19]. When adrenal glands are maximally stimulated by endogenous ACTH in stressful conditions such as tuberculosis, serum cortisol levels will be high and therefore exogenous ACTH may fail to further stimulate the adrenal glands [20]. We did not find any correlation between basal cortisol and D cortisol during standard dose ACTH stimulation test, but weak negative correlations were found between basal cortisol and D cortisol of low dose ACTH and glucagon stimulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is still one of the most important infectious agents that causes adrenal involvement [27]. Kelestimur et al [29] and Gulmez et al [28] found that adrenal glands were enlarged during acute pulmonary tuberculosis, followed by a later decrease in the size of the adrenals at the end of the therapy, and they reported that adrenocorticoid function is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies have now shown increased serum cortisol levels in HIV-infected patients [22,23]. The adrenal glands may be involved and enlarged by granulomatous infections (such as tuberculosis, histoplasmosis and blastomycosis), HIV and related infections [24][25][26][27][28][29]. Tuberculosis is still one of the most important infectious agents that causes adrenal involvement [27].…”
Section: Discussionmentioning
confidence: 99%